Ionospheric F-region observations over American sector during an intense space weather event using multi-instruments - de Abreu, A.J. (2017)
The critical interaction between the magnetosphere and ionosphere during intense geomagnetic storms continues to be important to space weather studies. In this investigation, we present and discuss the ionospheric F-region observations in the equatorial, low- and mid-latitude regions in both hemispheres over American sector during the intense geomagnetic storm on 01–03 June 2013. The geomagnetic storm reached a minimum Dst of −119 nT at 0900 UT on 01 June. For this investigation, we present vertical total electron content (VTEC) and phase fluctuations (in TECU/min) from a chain of 10 GPS stations and the ionospheric parameters foF2 and h′F from a chain of 4 digital ionosonde stations, covering from equatorial to mid-latitudes regions over American sector during the entire storm-time period 31 May–03 June 2013. In addition, the plasma density observed from DMSP satellites is presented. The results obtained show that during the sudden impulse/SSC and throughout the main phase of the storm, a large positive phase was observed in mid-latitudes of the northern hemisphere, which could be due to changes in the thermospheric wind circulation. On the other hand, in the mid-latitudes of the southern hemisphere, no deviations are observed in VTEC and foF2 when compared to the quiet period. During the long recovery phase of the storm on 01–02 June, a north-south asymmetry is observed in the F-region. The study confirms the dominant role of the thermospheric winds on north-south asymmetry in the ionospheric F-region. The ionospheric irregularities are found to be confined in the equatorial region, of the bottomside spread-F type, before and during the geomagnetic storm. It shows that the geomagnetic storm did not affect the generation or suppression of ionospheric irregularities at the stations investigated.